2018
DOI: 10.1021/acs.inorgchem.8b02390
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Camphor-Derived Bis(pyrazolylpyridine) Rhodium(III) Complexes: Structure–Reactivity Relationships and Biological Activity

Abstract: Two novel rhodium­(III) complexes, namely, [RhIII(X)­Cl3] (X = 2 2,6-bis­((4S,7R)-7,8,8-trimethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)­pyridine or 2,6-bis­((4S,7R)-1,7,8,8-tetramethyl-4,5,6,7-tetrahydro-1H-4,7-methanoindazol-3-yl)­pyridine), were synthesized from camphor derivatives of a bis­(pyrazolylpyridine), tridentate nitrogen-donor chelate system, giving [RhIII(H2L*)­Cl3] (1a) and [RhIII(Me2L*)­Cl3] (1b). A rhodium­(III) terpyridine (terpy) ligand complex, [RhIII(terpy)­Cl3] (1c), was also synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 90 publications
4
33
0
Order By: Relevance
“…[16] The binding affinity of complexes shown in Figure 1 to CT-DNA and BSA was studied using by different experimental methods. [33][34][35][36] The published results showed that the studied Pd(II) and Pt(II) complexes (1-4) have a very high binding affinity toward DNA molecule ( Table 2). Pt(II) complexes exhibited much higher binding affinity than Pd(II) complexes.…”
Section: Interactions With Ct-dna and Bsamentioning
confidence: 97%
See 4 more Smart Citations
“…[16] The binding affinity of complexes shown in Figure 1 to CT-DNA and BSA was studied using by different experimental methods. [33][34][35][36] The published results showed that the studied Pd(II) and Pt(II) complexes (1-4) have a very high binding affinity toward DNA molecule ( Table 2). Pt(II) complexes exhibited much higher binding affinity than Pd(II) complexes.…”
Section: Interactions With Ct-dna and Bsamentioning
confidence: 97%
“…The kinetic and mechanism of the substitution reactions of studied complexes (Figure 1) with important biological ligands such as thiourea (tu), L-methionine (L-met), L-cysteine (L-cys), glutathione (GSH) and guanosine-5'-monophosphate (5'-GMP) were studied. [33][34][35][36] Some obtained results are given in the Table 1.…”
Section: Substitution Reactionsmentioning
confidence: 99%
See 3 more Smart Citations